2007
DOI: 10.1021/ja069035a
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Dimeric Pyrrole−Imidazole Alkaloids:  Sceptrin, Ageliferin, Nagelamide E, Oxysceptrin, Nakamuric Acid, and the Axinellamine Carbon Skeleton

Abstract: The dimeric pyrrole imidazole natural products are a growing class of alkaloids with exotic connectivity, unique topologies, high nitrogen content, and exciting bioactivities. This full account traces the evolution of a strategy that culminated in the first total syntheses of several members of this family, including sceptrin, ageliferin, nagelamide E, nakamuric acid (and its methyl ester), and oxysceptrin. Details on the fascinating conversion of sceptrin to ageliferin, which has been used to produce gram qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
134
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(138 citation statements)
references
References 64 publications
3
134
0
1
Order By: Relevance
“…[7,8,[14][15][16][17] Previously, we used the 10′-hydroxy group of 4 (protected ent-10′-hydroxydibromoageliferin) to set up the desired spiro-configuration of 2a through directed oxidation.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…[7,8,[14][15][16][17] Previously, we used the 10′-hydroxy group of 4 (protected ent-10′-hydroxydibromoageliferin) to set up the desired spiro-configuration of 2a through directed oxidation.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…Recently, Romesberg, Baran, and co-workers have found that 1a and 1b display promising activity against both Gram-positive and Gram-negative bacteria and 1a causes membrane destabilization in Escherichia coli. [3] Among several labs that study the synthesis of dimeric pyrroleimidazole alkaloids 1-3, [3][4][5][6][7][8][9][10][11][12][13][14][15][16] Carreira et al reported the first synthetic strategy directed towards 1 [6] using a Diels-Alder reaction to establish its fully functionalized cyclopentyl core. Romo and co-workers subsequently disclosed an oxidative ring-contraction approach that was inspired by Scheuer's biosynthetic hypothesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Imidazole chemistry currently attracts considerable attention, where the imidazole derivatives are widely applied as N-ligands coordinating transition metals [2][3]. The application of imidazoles in medicinal chemistry [4] or chemistry of natural products/alkaloids [5][6] or of 1,3-disubstituted imidazole salts as ionic liquids [7][8] are also well known. Although a few examples of the synthesis and applications of optically active imidazole derivatives have been published [9][10][11][12][13], development of an efficient synthesis of such derivatives still requires more attention.…”
Section: Introductionmentioning
confidence: 99%
“…A beautiful transannular Michael reaction cascade sequence is the heart and soul of the salvinorin A synthesis by Evans and co-workers. 16 Baran and co-workers 17 provide a detailed account of their syntheses of several dimeric pyrrole-imidazole alkaloids by routes that utilize the fundamental chemistry of the 2-aminoimidazole heterocycle as well as a strategically novel fragmentation of an oxaquadricyclane intermediate. The synthesis of (+)-nakadomarin A by Kerr and Young 18 showcases the utility of a nitrone-cyclopropane cycloaddition to generate the pyrrolidine functionality within the tetracyclic core.…”
mentioning
confidence: 99%